2022
DOI: 10.1007/s13399-022-02362-y
|View full text |Cite
|
Sign up to set email alerts
|

Zero-valent iron supported-lemon derived biochar for ultra-fast adsorption of methylene blue

Abstract: Green-based materials represent a new promising class of ecofriendly and economic adsorbents. Herein, nano zero-valent iron supported-lemon derived biochar (NZVI-LBC) was prepared for the first time and examined in the adsorptive removal of methylene blue as a model pollutant. Different characterization tools were used to ensure the successful fabrication of the NZVI-LBC composite including FTIR, XRD, TEM, XPS, VSM, BET, and zeta potential analysis. It was found that the fabricated NZVI–supported biochar compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…It was concluded that MgO provided more active sites which agrees with Lihua et al 91 One of the difficulties of phosphate removal is its presence in multiple forms where it exists as H 3 PO 4 (pH < 2), H 2 PO 4 À (pH 2-7), HPO 4 2À (pH 7-11), and PO 4 3À (pH > 11). Alg-MgO@BT showed a high adsorption capacity towards phosphate ions over a wide pH range (3)(4)(5)(6)(7)(8)(9)(10) where the phosphate removal efficiency exceeded 99% at a pH lower than 7. This may be anticipated from the strong electrostatic interaction between H 2 PO 4 À and HPO 4 2À species and the positively charged Alg-MgO@BT.…”
Section: Clay-modied Alginatementioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that MgO provided more active sites which agrees with Lihua et al 91 One of the difficulties of phosphate removal is its presence in multiple forms where it exists as H 3 PO 4 (pH < 2), H 2 PO 4 À (pH 2-7), HPO 4 2À (pH 7-11), and PO 4 3À (pH > 11). Alg-MgO@BT showed a high adsorption capacity towards phosphate ions over a wide pH range (3)(4)(5)(6)(7)(8)(9)(10) where the phosphate removal efficiency exceeded 99% at a pH lower than 7. This may be anticipated from the strong electrostatic interaction between H 2 PO 4 À and HPO 4 2À species and the positively charged Alg-MgO@BT.…”
Section: Clay-modied Alginatementioning
confidence: 99%
“…Although we all have to be conscious of the imperative need for water conservation, [1][2][3][4][5] the aggravation of water pollution has grown day by day. [6][7][8][9] This catastrophic problem results from the disposal of numerous pollutants into water bodies, 10,11 particularly phosphate owing to its presence in nature and excessive uses in various elds. 12 It is well known that the majority of phosphorus is wrapped up in rocks and sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Water pollution is considered one of the most important critical problems facing countries, since wastewater poses a significant threat to the ecosystem as well as human health 1 . One source of contamination is dye discharge from industries such as textile, paper, leather tanning, food processing, plastics, cosmetics, rubber, printing and dye manufacturing 2 4 . Methylene blue (MB) is a highly stable cationic dye which readily aggregates and highly soluble even at minimal concentrations causing harmful impacts 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been employed for dyes remediation from contaminated water such as advanced oxidation, membrane filtration, photocatalytic degradation, and adsorption 10 14 . Adsorption is recognized one of the most promising treatment technologies for the removal of various harmful contaminants from wastewater owing to its excellent features comprising higher efficacy, low-cost production and simple processing 4 , 15 17 . Cellulose is the most abundant natural a polysaccharide polymer.…”
Section: Introductionmentioning
confidence: 99%
“…For the past two decades, researchers around the globe gave more attention to treating dyes in wastewater via adsorption processes. Due to its design flexibility, lack of treatment byproducts, ease of service, high efficacy, reusability, low cost, ease of operation, and insensitivity to biological materials in aqueous settings, the adsorption approach is the most widely used remediation method (Abd El-Monaem et al, 2022;Eltaweil et al, 2022). Among all types of adsorbents, activated carbon (AC) derived from biomass and agricultural wastes has gained popularity due to two main reasons-being economically feasible and having excellent adsorption performance.…”
Section: Introductionmentioning
confidence: 99%